Managing empathic political communication: Digital identity of Indonesian women legislators on Instagram - Syam Maella, Nur'annafi Farni; Setia Wardhani, Widya Desary; Pramudiana, Ika Devi; Aranggraeni, Renda; Sjuchro, Dian Wardiana (Manajemen Komunikasi, 2026)
Background: In the ever changing world of digital politics, women in politics often have to cope with the double challenge of preserving their institutional authority while also meeting gendered expectations of being relevant. Empathy is frequently seen as an inherent personality trait; nonetheless, its use as a strategic tool in digital political strategy remains inadequately explored, particularly within the framework of the Indonesian legislature. Purpose: This study aims to investigate how empathic political communication is strategically managed and configured as a form of symbolic capital by female members of the Indonesian House of Representatives on social media. Methods: Employing qualitative multimodal content analysis, this study examines the textual, visual, and interactional elements of posts published between July and October 2025. Results: The findings show the empathy functions not only as an emotional expression but also as a strategic communication resource. This in configured through four main patterns: building moral legitimacy, gender-based political branding, crisis responsive communication, and grassroot relation engagement. These patterns produce political identities such as moral advocates, caring mothers leaders, institutional guardians, and grassroots allies. Thus, empathy operates as a symbolic political capital used to strengthen legitimacy, maintain public trust, and negotiate gender expectations in digital politics. Conclusion: The study concludes that empathetic social media communication is a political strategy deliberately cultivated by female legislators to navigate authority, legitimacy, and gender-specific public expectations, rather than being merely spontaneous emotional expressions. In the Indonesian legislature, empathy is an important symbolic instrument for building a genuine digital political identity while maintaining in touch with the people. Implications: This research contributes to the literature by conceptualizing empathy as a communication management resource rather than a purely emotional trait.